Association Rules Menggunakan Algoritma FP-Growth Untuk Tata Letak Di Koperasi IT DEL - Hutapea, Oppir (Program Studi Teknik Informatika Universitas Multi Data Palembang, 2024)
Koperasi IT Del is located in IT Del campus that sells a range of office and school supplies, drinks, and snacks. For almost 20 years, the Koperasi IT Del has recorded and arranged goods manually, disregarding the needs or purchasing patterns of its clientele. The owners frequently fail to see how consumer behavior affects the sales of the cooperatives they oversee. Owners may find it easier to access their consumers' associative nature if they can identify user behavior and purchasing patterns. FP-Growth is a method that solves item layout issues by utilizing transaction or historical data that is already accessible. With a minimum support value of 24% and a minimum confidence level of 60%, this investigation yielded 47 association rules. 24 attributes that would be used from transaction history data that had already been verified were acquired from the data transformation results that were performed. The end consequence is that each association rule forms a close-knit product arrangement or position based on the item set that is commonly purchased. The Cimory UHT Matcha 20 ml box is positioned next to the 42 g Roma Coconut Cream Chocolate product (48.1%), then the My-Gell Blue Pen (47.3%), and finally the Standard AE7 Red Pen (48.1%), which is positioned next to the 42 g Roma Coconut Cream Chocolate product (48.1%), and finally next to the Nescafe Original 240 ml (47.3%).